P033: Procedural skills training in emergency medicine physicians within the Edmonton zone: a needs assessment. (May 2020) - Schonnop, R.; Stauffer, B.; Gauri, A.; Ha, D.
Abstract : Introduction: Procedural skills are a key component of an emergency physician's practice. The Edmonton Zone is a health region that comprises twelve tertiary, urban community and rural community emergency departments (EDs) and represents over three hundred emergency physicians. This study describes the current attitudes toward procedural skill competency, current procedural skill practices, and the role for educational skills training sessions among emergency medicine physicians within a geographical health region. Methods: Multicenter descriptive cross-sectional survey of all emergency medicine physicians working at 12 emergency departments within the Edmonton Zone in 2019 (n = 274). The survey underwent several phases of systematic review; including item generation and reduction, pilot testing, and clinical sensibility testing. Survey items addressed current procedural skill performance frequency, perceived importance and confidence, current methods to maintain competence, barriers and facilitating factors to participation in a curriculum, preferred teaching methods, and desired frequency of practice for each procedural skill. Results: Survey response rate was 53.6%. Variability in frequency of performed procedures was apparent across the type of hospital sites. For majority of skills, there was a significantly positive correlation between the frequency at which a skill was performed and the perceived confidence performing said skill. There was inconsistency and no significant correlation with perceived importance, perceived confidence, or frequency performing a given skill and the desired frequency of training for that skill. Course availability (76.2%) and time (72.8%) are the most common identified barriers to participation in procedural skills training. Conclusion: This study summarized the current emergency department procedural skill practices and attitudes toward procedural skill competency and an educational curriculum among emergency medicine physicians in Edmonton. This represents a step towards targeted continuing professional development in the growing realm of competency-based medical education.